PARADIGME, TEORII, MODELE DE INTERVENȚIE ALE CONSILIERII PENTRU CARIERĂ - Roxana AXINTE (Moldova State University, 2018)
Articolul prezintă o analiză a conceptelor teoretice, care se regăsesc la baza fundamentării demersului practic, realizat de către specialiști, în nișa activităților de consiliere pentru carieră. Sunt prezentate și analizate conceptele de paradigmă, teorie, model de acțiune/ intervenție. Integrarea informațiilor teoretice, aparținând mai multor teorii specifice de consiliere, se va regăsi într-un model de intervenție, asumat de către fiecare consilier. PARADIGMS, THEORIES, INTERVENTION MODELS IN CAREER COUNSELLING This article presents an analysis of the theoretical concepts providing the justifying basis for the specialists' practical approach in the career counselling's activities niche. We present and analyse the concepts of paradigm, theory, action/ intervention model. Integration of the theoretical knowledge borrowed from multiple career counselling specific theories leads to one's own intervention model to be developed by each career counsellor.